Influence of Fiber Diameter of Polycaprolactone Nanofibrous Materials on Biofilm Formation and Retention of Bacterial Cells - Lencova, Simona; Stindlova, Marta; Havlickova, Kristyna; Jencova, Vera; Peroutka, Vaclav; Navratilova, Katerina; Zdenkova, Kamila; Stiborova, Hana; Hauzerova, Sarka; Kostakova, Eva Kuzelova; Jankovsky, Ondrej; Kejzlar, Pavel; et al. (ACS applied materials & interfaces, 2024)
To develop microbiologically safe nanofibrous materials, it is crucial to understand their interactions with microbial cells. Current research indicates that the morphology of nanofibers, particularly the diameter of the fibers, may play a significant role in biofilm formation and retention. However, it has not yet been determined how the fiber diameter of poly-ε-caprolactone (PCL), one of the most widely used biopolymers, affects these microbial interactions. In this study, two nanofibrous materials electrospun from PCL (PCL45 and PCL80) with different fiber diameter and characteristic distance δ between fibers were compared in terms of their ability to support or inhibit bacterial biofilm formation and retain bacterial cells. Strains of Escherichia coli (ATCC 25922 and ATCC 8739) and Staphylococcus aureus (ATCC 25923 and ATCC 6538) were used as model bacteria. Biofilm formation rate and retention varied significantly between the E. coli and S. aureus strains (p < 0.05) for the tested nanomaterials. In general, PCL showed a lower tendency to be colonized by the tested bacteria compared to the control material (polystyrene). Fiber diameter did not influence the biofilm formation rate of S. aureus strains and E. coli 25922 (p > 0.05), but it did significantly impact the biofilm formation rate of E. coli 8739 and biofilm morphology formed by all of the tested bacterial strains. In PCL45, thick uniform biofilm layers were formed preferably on the surface, while in PCL80 smaller clusters formed preferably inside the structure. Further, fiber diameter significantly influenced the retention of bacterial cells of all the tested strains (p < 0.001). PCL45, with thin fibers (average fiber diameter of 376 nm), retained up to 7 log (CFU mL-1) of staphylococcal cells (100% retention). The overall results indicate PCL45's potential for further research and highlight the nanofibers' morphology influence on bacterial interactions and differences in bacterial strains' behavior in the presence of nanomaterials.
Keywords: morphology; Nanofibers; bacteria; nanofibers; retention; Polyesters; biofilmy; biofilm; Escherichia coli; nanovlákna; polycaprolactone; Biofilms; Staphylococcus aureus; polyestery